Use the product rule to differentiate the given function with respect to x:

x^2(x+3)^4

u=x^2

v=(x+3)^4

du/dx=2x

dv/dx=4

y=4x^2+2x(x+3)^4

I do not know how to get to the answer from here but the answer is

6x(x+1)(x+3)^3

Printable View

- April 13th 2010, 01:59 AMjuliakDifferentiation using product rule
Use the product rule to differentiate the given function with respect to x:

x^2(x+3)^4

u=x^2

v=(x+3)^4

du/dx=2x

dv/dx=4

y=4x^2+2x(x+3)^4

I do not know how to get to the answer from here but the answer is

6x(x+1)(x+3)^3 - April 13th 2010, 02:08 AMDebsta
- April 13th 2010, 03:52 AMe^(i*pi)
Your dv/dx should read